Makam Eyang Ki Kebo Kenongo:Titik Temu Sejarah Lokal, Spiritualitas Jawa, Dan Arsitektur Islam Awal: Eyang Ki Kebo Kenongo Tomb: The Intersection Of Local History, Javanese Spirituality, And Early Islamic Architecture - Fakehufidin; Viky Khoirul Fuady; Yahya Nur Fadillah (Fakultas Adab dan Bahasa UIN Raden Mas Said Surakarta, 2025)
This research examines the Tomb of Ki Kebo Kenongo in Pengging, Boyolali, as a site rich in historical, archaeological, and religious values in the context of Javanese culture. Ki Kebo Kenongo, or Ki Ageng Pengging, was an important figure during the transition from the Majapahit Kingdom to the Demak Sultanate, known both as a nobleman and as a spiritual figure of Sheikh Siti Jenar's disciple. An interdisciplinary approach is used in thisresearch, including the historical method to trace the genealogy, socio-political role, and spiritual teachings of Ki Kebo Kenongo; the archaeological approach to analyze the structure, materials, and ornaments of the tomb; and the religio-cultural approach to understand the pilgrimage tradition that is still alive in the community. The results show that this tomb is an important spiritual center, reflecting the combination of Islamic values with local wisdom and Javanese culture. The architecture of the tomb shows the acculturation of Hindu-Buddhist and early Islam, with pilgrimage practices reflecting the diversity of the community's religious expressions. Pilgrimage traditions such as prayer recitation, flower sowing, and kenduri emphasize the function of the tomb as a spiritual space as well as a symbol of cultural identity. This study emphasizes the importance of recognizing local sites as part of Indonesia's cultural heritage and national history